(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
Tuberculosis is the second biggest infectious disease killer after coronavirus. In this paper, we analyze a mathematical model of in-host tuberculous granuloma, obtaining the basic reproduction number, as well as the existence and stability of equilibrium points. The sensitivity analysis provides parameters that have a significant effect on model dynamics. Finally, changes in the number of immune cells, infected macrophages and Mycobacterium tuberculosis are analyzed by numerical simulation of three disease states: clearance, latent infection and active tuberculosis. The results suggest that the immune mechanism determing whether an infected individual will suffer from active or latent tuberculosis is the ability of activated infected macrophages to kill Mycobacterium tuberculosis.